(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
This paper describes the relationship of computer science in engineering and its effect on the organization of the engineer’s work, for this purpose, a historical framework of engineering is outlined, some engineering definitions are presented, functions and skills are described. engineer, computer science and its contributions to engineering, as well as in university computer training of the engineer. For the elaboration of the work, a bibliographic revision was made, exploration of the study programs of the engineering careers given in some of the local universities, and revision of some software applications used in the functions of the engineer.